1996
DOI: 10.1103/physrevd.54.r3693
|View full text |Cite
|
Sign up to set email alerts
|

Weak scale superstrings

Abstract: Recent developments in string duality suggest that the string scale may not be irrevocably tied to the Planck scale. Two explicit but unrealistic examples are described where the ratio of the string scale to the Planck scale is arbitrarily small. Solutions which are more realistic may exist in the intermediate coupling or "truly strong coupling" region of the heterotic string. Weak scale superstrings have dramatic experimental consequences for both collider physics and cosmology. 3/96 *

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
427
0
7

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 559 publications
(440 citation statements)
references
References 33 publications
6
427
0
7
Order By: Relevance
“…Theories with large compact extra dimensions of TeV size [64][65][66][67][68][69][70][71][72] have enriched dramatically the perspectives of the search for physics beyond the Standard Model. Among the possible higher-dimensional realizations, sterile neutrinos propagating in such extra dimensions [73][74][75][76] may provide interesting alternatives for generating the observed light neutrino masses.…”
Section: Extra Dimensionsmentioning
confidence: 99%
“…Theories with large compact extra dimensions of TeV size [64][65][66][67][68][69][70][71][72] have enriched dramatically the perspectives of the search for physics beyond the Standard Model. Among the possible higher-dimensional realizations, sterile neutrinos propagating in such extra dimensions [73][74][75][76] may provide interesting alternatives for generating the observed light neutrino masses.…”
Section: Extra Dimensionsmentioning
confidence: 99%
“…In the original string-theoretic considerations [2], the inverse length 1/R of the extra compact dimensions and the string mass M s turned out to be closely tied to the 4-dimensional Planck mass M P = 1.9 × 10 16 TeV, with all involved mass scales being of the same order. More recent studies, however, have shown [3,4,5,6,7] that there could still be conceivable scenarios of stringy nature where 1/R and M s may be lowered independently of M P by several or many orders of magnitude. Taking such a realization to its natural extreme, Ref.…”
Section: Mc-th-2002-06 Wue-itp-2002-025mentioning
confidence: 99%
“…The structure of the conventional QED Lagrangian is simply carried over to the five-dimensional case. The field content of the theory is given by a single gauge-boson A M transforming as a vector under the Lorentz group SO (1,4). In the absence of the gauge-fixing and ghost terms, the 5D-QED Lagrangian is invariant under a U(1) gauge transformation…”
Section: -Dimensional Abelian Modelsmentioning
confidence: 99%
“…The sources of this additional interaction is nothing but the scalar field φ defined in (4). Therefore, the main novelty in A(k 2 ) lies in the third and fourth lines at right-hand side of (15) which is recognized to be generated by the exchange of a scalar field with non-vanishing bare mass-squared (17).…”
Section: Gravitational Interactions From F (R) Gravitymentioning
confidence: 99%
“…The idea [1][2][3] that the scale of quantum gravity can be much lower than the Planck scale, possibly as low as the electroweak scale itself [4,5] since this extreme is not excluded by the present experimental bounds [6], has opened up novel lines of thought and a number of phenomena which possess observable signatures in laboratory, astrophysical and cosmological environments.…”
Section: Introductionmentioning
confidence: 99%